Neglected intrapulmonary arteriovenous anastomoses: A comparative study of pulmonary right-to-left shunts in patients with patent foramen ovale - Chen, Anni; Zhu, Jianbo; Zhu, Lei; Tang, Yunyi; Li, Yun; Zhang, Qi; Zhao, Yeping; Ma, Caiye; Liu, Xiatian (Frontiers in Cardiovascular Medicine, 2023)
Objective Pulmonary right-to-left shunt (P-RLS) and patent foramen ovale right-to-left shunt (PFO-RLS) often appear in combination, and there are often differences and connections between them. Intrapulmonary arteriovenous anastomoses (IPAVAs), as part of P-RLS, are often overlooked because there are no technologies to detect and identify them. This study aimed to further clarify the incidence and characteristics of P-RLS with the help of contrast transesophageal echocardiography (c-TEE) and contrast transthoracic echocardiography (c-TTE), providing a reference for clinically relevant research and patent foramen ovale (PFO) management disposal decisions. Methods We retrospectively investigated 414 subjects who came to our hospital for c-TEE from October 2021 to July 2022, and all subjects completed c-TTE simultaneously. 7 Patients who were newly diagnosed with an atrial septal defect were excluded. Eventually, 407 patients were included in this study. Among them, 157 patients with PFO (58 patients were treated with PFO closure subsequently) and 250 patients without PFO confirmed by c-TEE were finally enrolled. In the process, we observed and analysed the presence of P-RLS. Results A total of 407 patients were included in the final analysis and divided into PFO group (N = 157) and non-PFO group (N = 250) according to the results of c-TEE. Whether at rest or after Valsalva maneuver, the incidence of P-RLS was significantly higher under c-TEE than under c-TTE in the two groups (P < 0.001). For both c-TTE and c-TEE, the incidence of P-RLS was slightly higher after Valsalva maneuver than at rest, but the difference was not significant (c-TTE: rest vs. Valsalva maneuver, P = 0.214; c-TEE: rest vs. Valsalva maneuver, P = 0.076). The Valsalva maneuver increased the incidence of P-RLS in the group without PFO, which was more significant in c-TEE (c-TTE: rest vs. Valsalva maneuver, P = 0.591; c-TEE: rest vs. Valsalva maneuver, P = 0.008). In both groups, the P-RLS semiquantitative grading was statistical significance under different states and examinations (P < 0.001). Conclusion The vast majority of P-RLS are grade 1–2 and are derived from physiological IPAVAs. Even so, attention should be given to the differentiation between P-RLS and PFO-RLS. c-TEE is an effective method to detect P-RLS; however, the recruitments of c-TEE and Valsalva maneuver to P-RLS should be noted.